EDUKASI METODE PROMOSI KESEHATAN BAGI KADER POSYANDU BALITA DI WILAYAH KERJA PUSKESMAS WANASARI - Ice Marini; Lyliana Endang Setianingsih; Anom Dwi Prakoso (Jurnal Abdi Insani, 2023)
Introduction (Background): Data form the Ministry of Health in 2019, active posyandu in Indonesia was 65.42%, while the national target was 80%. The Bekasi District Health Service in its health profile stated that coverage for weighing toddlers in 2020 was 33.93%, decrease from coverage in 2019, this occurred due to the pandemic. Furthermore, the health office instructed health workers and cadres to reopen Posyandu dan carry out innovation activities such as developing promotional media for Posyandu service. Objective: The aim of as developing promotional media for Posyandu service. Objective: The aim of this community service is to increase cadres knowledge about health promotion media that can be used in Posyandu services and to carry out assistance activities in the implementation of Posyandu. Method: This community service is carried out through education for Posyandu cadres RW 11. Education is provided with pretest and posttest activities to measure increased knowledge. Mentoring activities are also carried. Result: The result of the activity showed an increase in knowledge with an average pretest score of 45.3 to 77.6 on the posttest. The cadres chose to make a flyer as a promotional invitation to go to Posyandu which was distributed in the WhatsApp group for mothers of toddlers. For the slogan for inviting people to the Posyandu, cadres used the slogan â€œGerakan Oppa (Opss, jangan lupa ke Posyandu)â€ to be included on a banner that could be clearly read by Posyandu visitors. During the mentoring activity, cadres were given several posters to display in Posyandu. Then a pocket book with the title â€œhealth promotion methods in Posyanduâ€ was also given to cadres as a guide for choosing promotion methods that were appropriate for the local Posyandu. Conclusion: There is an increase in knowledge form educational activities about health promotion media at Posyandu. Cadres chose flyer as the promotional method used at Posyandu.